OPTIMALISASI ZAKAT PRODUKTIF DALAM PENGENTASAN PROBLEM KEMISKINAN - Ainol Yaqin (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2015)
Tithe is one of the pillars of Islam which must be carried out every Muslims throughout the world. One of the studs and the its collapse of the Islamic religion relation to the enforcement of the tithe Shari'ah. Because Tithe functions in reductin and eradicate problems of poverty so that an abundance of possessions does not circle in the realm of mere property owner. With the Tithe at least poverty can be minimized and even eliminated, because of the danger of poverty  often drags on gorge heathenism. In addition, expression of the rich get richer and the poor get poorer is no longer surrounds life. For realization of a prosperous society, free from poverty windings required optimization of  productive Tith. In this region, government and private intervention in the formation of Tithe institution, management, utilization , empowerment and distribution becomes defining  factor of the establishment success of Tithe shari'ah. When set of tithe treasure managed productively with regarding the mustahiq benefit then the problem winding of poverty will get to be decomposed the loose.